Silver nanoparticle-coated Bacteriophages: A novel therapeutic approach for combating Enterococcus faecalis in endodontic infections - Anabathula Praharsha; Alpa Gupta; Kanchan Bhardwaj; Lubhansha Kumar; Priya Khandelwal; Saumya Verma (Journal of Oral Biology and Craniofacial Research, 2025)
Introduction: Endodontic infections, particularly those caused by Enterococcus faecalis, are a major cause of treatment failure due to their resistance to conventional antimicrobial treatments. This study explores the use of silver nanoparticles to coat bacteriophages targeting E. faecalis, aiming to improve their antimicrobial properties and biocompatibility for endodontic applications. Materials and methods: Bacteriophages against Enteroccus faecalis were isolated from poultry samples using an agar overlay technique and purified through serial dilution and plaque assays. Silver nanoparticles were synthesized and coated onto the bacteriophages using a coacervation/precipitation method. The cytotoxicity of silver nanoparticles was assessed using an MTT assay on human gingival fibroblasts. Antimicrobial efficacy was evaluated through minimum inhibitory concentration (MIC) testing and zone of inhibition assays against Streptococcus mutans and Porphyromonas gingivalis. The structural characteristics of the silver nanoparticle-coated bacteriophages were analyzed using scanning electron microscopy (SEM). Results: The bacteriophage isolation was confirmed by distinct plaque formation on E. faecalis cultures. The MTT assay revealed minimal cytotoxicity of 0.05 % silver nanoparticles, with cell viability greater than 91 % at all time points. MIC testing indicated that 0.05 % silver nanoparticles effectively inhibited bacterial growth, with significant inhibition zones (16.83 mm for P. gingivalis and 14.50 mm for S. mutans). SEM analysis showed successful coating of the bacteriophages with silver nanoparticles, with clear morphological changes and increased surface roughness. Conclusion: Silver nanoparticle-coated bacteriophages represent a promising therapeutic approach to enhance bacteriophage stability and antimicrobial efficacy against E. faecalis in endodontic infections.